Economic mentality as the basis of the choice of the vector of social-economical system’s transformation - Sidorova, Aleksandra M. (Journal of the Belarusian State University. Economics, 2018)
The issues of institutional transformation of the social and economic system of the Republic of Belarus are discussed. The importance of studying the phenomenon of economic mentality and its role in the processes of transformation of the institutional system is substantiated. The results of the study of the modern economic mentality of the Belarusian people are presented. The modern type of economic mentality and its influence on the choice of the institutional vector of transformation are analyzed. A cluster is singled out, to which the economic system of the Republic of Belarus tends, recommendations are given for further transformation, and the existence of the track effect is assessed.
Keywords: economic mentality; institutional transformation; state-corporate type of economic mentality; track effect